Citric Acid Extraction in Citrus hystrix Peels as an Alternative Material for Reducing Water Hardness - Ni Nyoman Suciani; Irwan Said; Anang Wahid M. Diah (Jurnal Akademika Kimia, 2021)
Water hardness will have a destructive impact if consumed in a long time. Hard water contains high calcium contents, including inorganic calcium. The accumulation of calcium in the body at a specific time causing kidney stones, and some will settle in the blood that causing calcification which can be fatal to health. An alternative is needed to reduce the level of water hardness. This study aimed to determine the effect of using citric acid on citrus hystrix peels on water hardness. Citric acid was obtained through the maceration extraction method from citrus hystrix. The citric acid extract was made into several concentrations of 50, 100, and 150 ppm then added to hard water. Determination of decreased total water hardness after adding citric acid used method complexometry titration. The results of the analysis show that citric acid is able to reduce water hardness of the sample water from Palu city area.